Chronic exposure of bumblebees to neonicotinoid imidacloprid suppresses the entire mevalonate pathway and fatty acid synthesis - Erban, Tomas; Sopko, Bruno; Talacko, Pavel; Harant, Karel; Kadlikova, Klara; Halesova, Tatana; Riddellova, Katerina; Pekas, Apostolos (Journal of proteomics, 2019)
Determining the side effects of pesticides on pollinators is an important topic due to the increasing loss of pollinators. We aimed to determine the effects of chronic sublethal exposure of the neonicotinoid pesticide imidacloprid on the bumblebee Bombus terrestris under laboratory conditions. The analytical standard of imidacloprid in sugar solution was used for the treatment. Verification of pesticides using UHPLC-QqQ-MS/MS in the experimental bumblebees showed the presence of only two compounds, imidacloprid and imidacloprid-olefin, which were found in quantities of 0.57 ± 0.22 and 1.95 ± 0.43 ng/g, respectively. Thus, the level of the dangerous metabolite imidacloprid-olefin was 3.4-fold higher than that of imidacloprid. Label-free nanoLC-MS/MS quantitative proteomics of bumblebee heads enabled quantitative comparison of 2883 proteins, and 206 proteins were significantly influenced by the imidacloprid treatment. The next analysis revealed that the highly downregulated markers are members of the terpenoid backbone biosynthesis pathway (KEGG: bter00900) and that imidacloprid treatment suppressed the entire mevalonate pathway, fatty acid synthesis and associated markers. The proteomics results indicate that the consequences of imidacloprid treatment are complex, and the marker changes are associated with metabolic and neurological diseases and olfaction disruption. This study provides important markers and can help to explain the widely held assumptions from biological observations. SIGNIFICANCE: The major finding is that all markers of the mevalonate pathway were substantially downregulated due to the chronic imidacloprid exposure. The disbalance of mevalonate pathway has many important consequences. We suggest the mechanism associated with the novel toxicogenic effect of imidacloprid. The results are helpful to explain that imidacloprid impairs the cognitive functions and possesses the delayed and time cumulative effect.
Keywords: Endocrine disruptor; Mevalonic Acid; Fatty Acids; Insecticides; Pesticide exposure; Proteomics; kyselina mevalonová; Terpenoid backbone biosynthesis pathway; zvířata; Bombus terrestris; neonikotinoidy; Neonicotinoids; včely; insekticidy; mastné kyseliny; Nitro Compounds; dusíkaté sloučeniny; Bees; Imidacloprid-olefin; Animals